Serum levels of bone morphogenetic proteins 2 and 4 in patients with acute myocardial infarction - Kercheva, Maria; Gusakova, Anna M.; Ryabova, Tamara R.; Suslova, Tatiana E.; Kzhyshkowska, Julia; Ryabov, Vyacheslav V. (Cells, 2020)
Background: Bone morphogenetic proteins-2 and -4 (BMPs) have been implicated in left ventricular remodeling (LVR) processes such as an inflammation and fibrogenesis. We hypothesized that this knowledge could be translated into clinics. Methods: We studied the dynamics of serum levels of BMPs, its correlation with markers of LVR and with parameters of echocardiography in patients (n = 31) during the six-month follow-up period after myocardial infarction (MI). Results: Elevated serum levels of BMPs decreased by the six-month follow-up period. BMP-2 decreased from the first day after MI, and BMP-4 decreased from the Day 14. The elevated level of BMP-2 at Day 1 was associated with a lower level of troponin I, reperfusion time and better left ventricular ejection fraction (LV EF) at the six-month follow-up. Elevated serum level of BMP-4 at Day 1 was associated with a lower level of a soluble isoform of suppression of tumorigenicity 2 (sST2), age and reperfusion time. An elevated level of BMP-2 at the six-month follow-up was associated with higher levels of BMP-4, high-sensitivity C-reactive protein (hCRP) and sST2. High serum level of BMP-2 correlated with high levels of hCRP and matrix metalloproteinase (MMP)-9 on Day 7. High serum level of BMP-4 correlated with low levels of hCRP, MMP-9 at Day 3, sST2 at Day 1 and with decreased LV EF on Day 7. The findings of multivariate analysis support the involvement of BMP-2 in the development of post-infarction LVR. Conclusions: Our research translates experimental data about the BMPs in the development of adverse LVR into the clinic. Elevated serum levels of BMPs decreased by the end of the six-month period after MI. BMP-2 decreased from the first day and BMP-4 decreased from Day 14. BMP-2 and BMP-4 were associated with the development of LVR. Their correlations with markers of inflammation, degradation of the extracellular matrix, hemodynamic stress and markers of myocardial damage further support our hypothesis. Diagnostic and predictive values of these BMPs at the development of post-infarction LVR in vivo should be investigated further.
Gesehen am 07.07.2025